Changes in seasonal influenza vaccination uptake among older adults during and after the COVID-19 pandemic: Repeated random telephone surveys - Xue Liang; Cichong Cai; Fuk-Yuen Yu; Danhua Ye; Yuan Fang; Phoenix K. H. Mo; Zixin Wang (Human Vaccines & Immunotherapeutics)
People’s risk of contracting seasonal influenza increased after COVID-19 control measures were relaxed. This study investigated the changes in seasonal influenza vaccination (SIV) uptake and its determinants among older adults during and after the COVID-19 period. Two rounds of random telephone surveys were conducted among 440 and 373 community-living individuals aged ≥65 y, the first between November 2021 and January 2022 and the second between October 2023 and January 2024. The difference in SIV uptake rate was not significant when comparing the second round with the first round (50.1% versus 45.0%, p = .48). Concerns related to the cost and inconvenience to receiving the SIV were associated with lower SIV uptake in the second round, but not the first round. Perceived higher risk of seasonal influenza and COVID-19 co-infection, perceived higher risk and more severe consequences of seasonal influenza, and perceived more benefits, receiving more suggestions from significant others and having higher self-efficacy related to SIV, were associated with higher SIV uptake in both surveys. Concerns that SIV and COVID-19 vaccinations would have negative impacts on each other, along with concerns about the side-effects of SIV, were associated with lower SIV uptake in both surveys. The rebound of seasonal influenza in the post-pandemic era highlights the needs to improve SIV uptake among older adults.